Effects of life skills education on emotional problems, self-esteem and coping mechanisms among institutional adolescents in Klang Valley, Malaysia - Mohammadzadeh, Marjan (2017)
Institutionalised children and adolescents are at greatly increased risk of serious psychological problems in their lifetime and exhibit various psychological, emotional and behavioural problems such as coping and adjustment problems, aggression, personality problems, low self-esteem, depression and stress. In light of the several mental and behavioural health issues among adolescents living in orphanages that require serious attention, the early detection of mental health challenges is important and can minimize these problems in adulthood. The current study aimed to determine, if a life skills-based intervention programme could improve the emotional health, self-esteem and coping skills among adolescents in Klang Valley orphanages. Using multi-stage random sampling and based on inclusion and exclusion criteria, 271 adolescents, aged 12 to 17 years old who experienced mild to extra severe score in one of the objectives of DASS21 questionnaire (depression, anxiety and/or stress) were selected to participate in the study. This was a parallel subject-masked randomized controlled trial (RCT) with pre-, post- and four-month follow-up tests comprising two groups: intervention and control groups were randomly selected to receive the intervention programme (Life skills education) or the placebo education programme (COMBI programme).The study instrument was a validated questionnaire booklet including: Depression, Anxiety and Stress Scale (DASS21), Rosenberg self-esteem scale (RSES) and Brief COPE scale. The intervention module was developed based on the WHO programme on life skills education and Coping-Stress Theory. Overall, 20 activities were developed for 12 intervention sessionsin the form of “The Guideline for Trainers” booklet during the development and piloting process. Intervention sessions were held approximately twice weekly for each home, each lasting abouttwo and half hours. Mixed between-within subjects ANOVA were performed to assess the differences in the means of continuous variables within the 3 stages at baseline, post-test and 4-month follow-up in the intervention and control groups.According to the results, there was a significant different in the mean score of depression (F=33.80, P<0.001, η2=0.11), anxiety (F=11.70, P=0.01, η2=0.04) , stress (F=28.13, P<0.001, η2=0.10) and self-esteem (F=19.03, P<0.001, η2=0.10) among 3 stage of time as well as interaction between group and time (F=31.04, P<0.001, η2=0.10; F=14.21, P<0.001, η2=0.05; F=15.67, P<0.001, η2=0.06; and F=13.29, P<0.001, η2=0.05) respectively for depression, anxiety, stress and self-esteem. Meanwhile, results of Mixed between-within subjects ANOVA showed there was not a significant difference in the mean score of depression (F=2.33, P=0.13) between groups.For coping methods, the intervention program was significantly effective on the mean scores of majority of fourteen coping methods among 3 stage of time (p<0.05), expect religion (F=5.63, p=0.13) and humor (F=0.98, p=0.37). There was also no significant difference between groups in the mean score of self-distraction (F=0.25, p=0.61), venting (F=2.62, p=0. 10) and acceptance (F=0.93, p=0.34) methods. Overall, the results of the current study showed the intervention program can be introduced as an effective plan for improving mental health and coping methods among Malaysian institutional adolescents.